S100A4 is expressed at site of invasion in rheumatoid arthritis synovium and modulates production of matrix metalloproteinases. Issue 12 (14th November 2006) - Šenolt, L; Grigorian, M; Lukanidin, E; Simmen, B; Michel, B A; Pavelka, K; Gay, R E; Gay, S; Neidhart, M
Abstract : The metastasis-associated protein S100A4 promotes the progression of cancer by regulating the remodelling of the extracellular matrix. The expression of S100A4 in vivo is shown and the functional role of S100A4 in the pathogenesis of osteoarthritis and rheumatoid arthritisis is explored. The expression of S100A4 in rheumatoid arthritis, osteoarthritis and normal synovial tissues was determined by immunohistochemistry. The expression of matrix metalloproteinase (MMP) mRNA was measured in rheumatoid arthritis and osteoarthritis synovial fibroblasts treated and untreated with S100A4 oligomer by real-time polymerase chain reaction. Levels of released MMPs were confirmed by ELISA in cell culture supernatants. S100A4 protein was expressed in rheumatoid arthritis and osteoarthritis synovial tissues, in contrast with normal synovium. S100A4 up regulated MMP-3 mRNA in rheumatoid arthritis synovial fluid, with a peak after 6 h. This resulted in release of MMP-3 protein. MMP-1, MMP-9 and MMP-13 mRNA were also up regulated in synovial fluid, but with different kinetics. MMP-14 mRNA showed no change. Thus, S100A4 protein is expressed in synovial tissues of patients with rheumatoid arthritis and osteoarthritis in contrast with healthy people. It induces the expression and release of MMP-3 and other MMPs from synovial fluid. The data suggest that S100A4-producing cells could be involved in the pathogenesis of osteoarthritis and rheumatoid arthritis, including pannus formation and joint destruction.